2007
DOI: 10.1021/jp072530o
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative Water Potential for Molecular Dynamics Simulations

Abstract: A new interatomic potential for dissociative water was developed for use in molecular dynamics simulations. The simulations use a multibody potential, with both pair and three-body terms, and the Wolf summation method for the long-range Coulomb interactions. A major feature in the potential is the change in the shortrange O-H repulsive interaction as a function of temperature and/or pressure in order to reproduce the densitytemperature curve between 273 K and 373 at 1 atm, as well as high-pressure data at vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
187
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(205 citation statements)
references
References 38 publications
18
187
0
Order By: Relevance
“…52 Recently, Mahadevan and Garofalini developed a dissociative water-silica forcefield based on water potentials by Guillot and Guissani. 53 Another forcefield used the BKS potential for silica and a SPC/E water model with Buckingham interactions for water-silica interfaces was developed by Hassanali and Singer. 54 Other water-silica potentials have been developed; 55,56 however, truly reactive potentials that can describe silica and water structures, reaction pathways, and energetics are rare.…”
Section: First-principles-based Simulations Of Glass-water Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…52 Recently, Mahadevan and Garofalini developed a dissociative water-silica forcefield based on water potentials by Guillot and Guissani. 53 Another forcefield used the BKS potential for silica and a SPC/E water model with Buckingham interactions for water-silica interfaces was developed by Hassanali and Singer. 54 Other water-silica potentials have been developed; 55,56 however, truly reactive potentials that can describe silica and water structures, reaction pathways, and energetics are rare.…”
Section: First-principles-based Simulations Of Glass-water Interactionsmentioning
confidence: 99%
“…Dissociation energy barriers of different Si Q n species (silicon oxygen tetrahedron with n bridging oxygen) on silica glass surfaces were investigated using the potential mean force approach with MD simulations. By using the dissociative watersilica potential developed by Mahadevan and Garofalini, 53 it was found that among the four (Q 4 → Q 3 , Q 3 → Q 2 , Q 2 → Q 1 , or Q 1 → Q 0 ) reactions, the Q 3 → Q 2 and Q 2 → Q 1 reactions have the highest activation energy of~14.1 kcal/mol, and is the rate limiting step in bulk silica dissolution. 19,24 These barriers are in the lower range of the experimental energy barriers of 14-24 kcal/mol and below values from cluster-based ab initio calculations (18-39 kcal/ mol).…”
Section: First-principles-based Simulations Of Glass-water Interactionsmentioning
confidence: 99%
“…A second assumption is that currently available classical (e.g, Pedone et al, 2008) and reactive force field models (Garofalini, 2001;Mahadevan and Garofalini, 2007;2008) can effectively be used to model the multicomponent glass structures and surfaces proposed for study. There is a possibility that additional force field development will be required.…”
Section: Overall Approachmentioning
confidence: 99%
“…Up to this point, the presentation covered only nontitratable water models. The parametrization of good dissociative water potentials (and their combination with force fields parameters for the other molecular species) is another critical issue and open question (Mahadevan and Garofalini 2008). In the same line, it has not been proven yet that the classical force fields parameters obtained at a given fixed experimental pH and salt conditions and routinely used to study the biomolecular phenomena are valid to explore all other interesting physical chemical regimes different than the ones used in the calibration process.…”
Section: Introductionmentioning
confidence: 99%